Why Chunking Should be Considered as an Explanation for Developmental Change before Short-Term Memory Capacity and Processing Speed - Jones, Gary (Frontiers in Psychology, 2012)
The chunking hypothesis suggests that during the repeated exposure of stimulus material, information is organized into increasingly larger chunks. Many researchers have not considered the full power of the chunking hypothesis as both a learning mechanism and as an explanation of human behavior. Indeed, in developmental psychology there is relatively little mention of chunking and yet it can be the underlying cause of some of the mechanisms of development that have been proposed. This paper illustrates the chunking hypothesis in the domain of nonword repetition, a task that is a strong predictor of a child’s language learning. A computer simulation of nonword repetition that instantiates the chunking mechanism shows that: (1) chunking causes task behavior to improve over time, consistent with children’s performance; and (2) chunking causes perceived changes in areas such as short-term memory capacity and processing speed that are often cited as mechanisms of child development. Researchers should be cautious when considering explanations of developmental data, since chunking may be able to explain differences in performance without the need for additional mechanisms of development.